THE CUSTOMER LOYALTY OF PATAS PURWAKARTA TRAIN SERVICE USERS - Riyaldi, Muhamad Sapta; Amrizal, Amrizal; Silalahi, Tiur Merry Bunga (Sekolah Tinggi Manajemen Transportasi (STMT) Trisakti, 2016)
The aim of this research is to find out the influence of service quality, ticket price, and customer satisfaction to the customer loyalty. It is a quantitative research using the data analysis method of Path Analysis. The results indicate that both variables of Service Quality (X1) and Ticket Price (X2) have a significant direct influence to the variable of Customer Satisfaction (Y1), whereas the variable of customer satisfaction has a significant indirect influence to the variable of Customer Loyalty (Y2) [through intervening the variable of customer satisfaction]. It is found in a sequence that the variables most influential to the increase of Customer Loyalty are: Service Quality, Â Customer Satisfaction, and the Ticket Price in the last rank.The results of path analysis indicate that service quality can directly influence the customer loyalty. It can be optimistically improved as maximal as possible through 5 factors having positive influences in enhancing customer loyalty. Meanwhile, Ticket Price still indirectly influences the customer loyalty and it can pesimistically still be enhanced through the policy on tariff and it is difficult to implement, only can be driven if the ticket price provided by the transport service provider is more competitive and more various as well as affordable for the consumer purchase power of that transport sevice.